Ti3AlC2 reinforced Fe-based high-temperature-resistant self-lubricating composite material and preparation method thereof

By using the non-stoichiometric compound TiCx as a binding agent in the Fe matrix and combining with the SPS sintering process, the problem of easy shedding of Ti3AlC2 is solved, and the mechanical and lubricating properties of the Fe-based self-lubricating composite material is significantly improved.

CN119753473APending Publication Date: 2025-04-04YANSHAN UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510037372.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-09
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

When Ti3AlC2 exists in the Fe matrix, it is prone to fall off, resulting in the overall performance and lubricating properties of the composite material being affected.

Method used

The non-stoichiometric compound TiCx is used as the binding agent to prepare Ti3AlC2 enhanced Fe-based self-lubricating composite material through SPS sintering process to improve the interface binding force between Ti3AlC2 and Fe matrix.

Benefits of technology

The mechanical properties and lubricating properties of the composite material are significantly improved, so that it has a stable friction coefficient in the range of 25~500℃ and reduces the wear rate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119753473A_ABST
    Figure CN119753473A_ABST
Patent Text Reader

Abstract

The invention discloses a high-temperature-resistant Fe-based self-lubricating composite material. Wherein the non-stoichiometric compound is a nitride, carbide or boride of a transition metal (Ti, V, Cr, Zr, Nb, Mo, Hf, Ta, W), and the solid lubricating phase comprises a ternary layered compound of a Mn + 1AXn (n = 1, 2, 3) family. Raw material mixing of the high-temperature-resistant Fe-based self-lubricating composite material comprises the step of mixing the Fe alloy raw material, the non-stoichiometric ratio compound raw material and the solid lubricating phase raw material through a ball-milling mixing method. Or the metal elementary substance powder of the Fe alloy component, the non-stoichiometric compound raw material and the solid lubricating phase raw material are mixed through a ball-milling mixing method, and the prepared composite powder is pre-pressed and formed. And finally, preparing a high-temperature-resistant Fe-based self-lubricating composite material sintered body by adopting a powder metallurgy sintering method. The high-temperature-resistant Fe-based self-lubricating composite material is synthesized by adopting various powder and sintered body preparation methods, and the comprehensive performance is excellent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of composite materials, and particularly to a preparation method of a Ti3AlC2 reinforced Fe-based high-temperature resistant self-lubricating composite material. Background Art

[0002] With the continuous research and development of Fe alloys and the continuous improvement of their performance, Fe-based self-lubricating composite materials are currently being attempted to be applied in rotating friction fields such as aerospace bearings and aerospace landing gears. Since ternary layered compounds Ti3SiC2 and Ti3AlC2 have excellent properties of both metals and ceramics, such as high melting point, high elastic modulus, good corrosion resistance and self-lubrication, they can be applied to wear-resistant materials, corrosion-resistant parts, etc., which has attracted the research of many scientific researchers.

[0003] Feng Shaoliang [Feng Shaoliang. Influence of Ti3SiC2 on the friction and wear properties of Fe-based sliding bearing materials [D]. Yanshan University, 2017.] prepared Ti3SiC2-Fe-based composites by the SPS method. It was found that the friction and wear properties of the prepared Fe-based composites were poor at room temperature and 500 °C, and their friction coefficients were 0.432 and 0.333 respectively, and the corresponding wear rates were 2.4×10 -4 mm 3 N -1 m -1 and 2.15×10 -4 mm 3 N -1 m -1 , which is mainly due to the poor interfacial bonding between Ti3SiC2 and the matrix. Therefore, Guan Yong [Guan Yong. Preparation and friction and wear properties of Ti3SiC2-TiC 0.4 -TiAl self-lubricating composite materials [D]. Yanshan University, 2019.] used the addition of non-stoichiometric TiC 0.4 as a binder to enhance the interfacial bonding between Ti3SiC2 and the matrix. It was found that effective friction reduction could be achieved for TiAl-based composites at 25 °C and 550 °C, which was attributed to TiC 0.4The interface between the matrix and Ti3SiC2 is more perfectly bonded, thus reducing the abrasive wear caused by the separation of Ti3SiC2 particles from the matrix, thereby reducing the friction coefficient and wear rate. At this time, the friction coefficient of the composite material at room temperature and 550°C is 0.47 and 0.41, respectively, and the corresponding wear rate is 0.095mg / m and 0.015mg / m. At the same time, studies have found that the bonding strength of metal bonds in different MAX phases is also different. Hu Jieqiong et al. [Hu Jieqiong, Xie Ming, Chen Jialin, et al. First principles study of the electronic structure and elastic properties of Ti3AC2 (A=Si, Sn, Al, Ge) [J]. Acta Physica Sinica, 2017, 66(5): 270-279.] calculated that the strength of the Ti-Si bond in Ti3SiC2 is higher than that of the Ti-Al bond in Ti3AlC2. This is the main reason for the difference in mechanical properties and surface characteristics between Ti3SiC2 and Ti3AlC2. Therefore, in this study, ceramic phase Ti3AlC2 was selected as a solid lubricant to improve the mechanical properties and wear resistance of Fe-based composites.

[0004] Chen Lin et al. studied Ti3AlC2 / Fe-based materials and obtained Ti3AlC2 / Fe composite materials under hot pressing conditions of 1300℃, 30MPa and 30min of heat preservation. After thermal shock at 800℃, the strength of the composite materials except 30vol.%Ti3AlC2 / Fe remained basically unchanged or slightly increased, and the fracture mode of the materials remained basically unchanged before and after thermal shock, showing good thermal shock resistance. This proved its good impact resistance. [Chen Lin, Zhai Hongxiang, Huang Zhenying, Xu Hao. Preparation and Mechanical Properties of Ti3AlC2 / Fe Composite Materials[J]. Journal of Synthetic Crystals, 2015, 4(11): 3288-3291.]; At this time, the study noticed that although Ti3AlC2 has good lubrication properties, if Ti3AlC2 cannot be well preserved after sintering, the lubrication effect cannot be achieved. At this time, Chen Xinhua et al. studied the mutual reaction between Ti3AlC2 and Fe at high temperature and found that when the sintering temperature was 760-1045℃, the reaction between Ti3AlC2 and Fe was weak and TiC began to form. 0.6phase, and theoretical analysis found that the precipitation of Al in Ti3AlC2 is the main factor causing Ti3AlC2 to react with Fe at a temperature far below its decomposition temperature. [Chen Xinhua, Zhai Hongxiang, Song Pengfei, Huang Zhenying. Reaction behavior of Ti3AlC2 and Fe at high temperature (English) [J]. Rare Metal Materials and Engineering, 2011, 40(S1): 499-502]; In previous studies, the dissolution temperature of Ti3AlC2 mixed metal materials is too low, which will lead to a large amount of decomposition of Ti3AlC2. Therefore, a suitable sintering temperature will make the material preparation successful. Wang Xiujuan et al. prepared Ti3AlC2-Cu material by chemical copper plating and then sintered it with copper powder and Ti3AlC2 material at 850℃ to obtain a uniformly distributed Ti3AlC2. Under a large friction pressure, the friction coefficient of Ti3AlC2 with a content of 15vol.% can reach as low as 0.15, and the wear performance is improved by nearly 20% after chemical copper plating. [Wang Xiujuan. Preparation and performance research of Ti3AlC2 / Cu composite materials [D]. Hefei University of Technology, 2014]; Chen Lulu et al. studied the temperature effect of Ti3AlC2 materials and Fe-based materials, and proposed that at 1400℃, when the volume content of raw material Ti3AlC2 changes from 10 vol.% to 40 vol.%, Al escapes from Ti3AlC2 to form TiCx, and then in-situ TiCx-Fe-based composite materials are prepared. [Chen Lulu. Influence of TiCx content on hot pressing preparation of TiCx-Fe-based composite materials [A]. Special Ceramics Branch of China Silicate Society. Abstracts of the 19th National High-tech Ceramics Academic Annual Conference [C]. Special Ceramics Branch of China Silicate Society: 2016: 1]; Li Jing et al. prepared Fe3Al powders with different Al contents by mechanical alloying combined with annealing treatment, and obtained Fe3Al intermetallic compound bulk materials by vacuum hot pressing sintering. The room temperature mechanical properties of Fe3Al sintered bulk materials are significantly improved compared with the cast state. Its room temperature flexural strength is 1000~1400 MPa, the compressive yield strength and compressive strain are 1150~1800 MPa and 10%~15% respectively, and the Rockwell hardness is 55~60HRC; the change of Al content has a certain effect on its microstructure and mechanical properties. [Li Jing, Yin Yansheng, Liu Yingcai, et al. Microstructure and mechanical properties of hot-pressed sintered FeAl intermetallic compounds [J]. Journal of Materials Heat Treatment (04).] Although the above research proves that Ti3AlC2 has good lubrication properties, Ti3AlC2 is easy to fall off from the matrix, resulting in the overall performance of the composite material, especially the lubrication performance being affected. Summary of the invention

[0005] The object of the present invention is to provide a Ti3AlC2 reinforced Fe-based self-lubricating composite material and a preparation method thereof, wherein the non-stoichiometric compound TiCx acts as a binder to solve the problem of Ti3AlC2 in the Fe matrix in the above-mentioned composite material.

[0006] High temperature resistant Fe-based self-lubricating composite materials, the mass fraction of Fe alloy in the high temperature resistant Fe-based self-lubricating composite materials is 25~50wt.%, non-stoichiometric compound TiC 0.4 The mass fraction of the solid lubricating phase Ti3AlC2 is 16.7~25wt.%, and the mass fraction of the solid lubricating phase Ti3AlC2 is 33.3~50wt.%.

[0007] The present invention also provides a method for preparing a high temperature resistant Fe-based self-lubricating composite material. In the preparation process, the method for preparing a high temperature resistant Fe-based self-lubricating composite material comprises the following steps: S1 preparation of a non-stoichiometric compound; S2 preparation of Fe alloy raw materials; S3 raw material mixing; S4 SPS sintering, wherein: S1. Preparation of non-stoichiometric compound raw materials: The preparation of TiCx powder can be found in China: CN108754275B; S2. Preparation of Fe alloy powder: Using the metal powder of the Fe alloy component as raw material, weighing each metal powder according to a predetermined ratio, and then adopting a mechanical alloying method to prepare Fe alloy powder, the ball-to-material ratio is 6:1, the rotation speed is 200r / min, and the ball milling time is 4h; S3, raw material mixing: including two methods: a. In an argon atmosphere, the Fe alloy powder, TiCx powder and Ti3AlC2 particles with a predetermined ratio are ball-milled to obtain a composite powder, with a ball-to-material ratio of 6:1, a rotation speed of 200 r / min, and a ball-milling time of 2 to 10 h; b. In an argon atmosphere, the Cu powder, Cr powder, Ni powder, Fe powder, TiCx powder and Ti3AlC2 particles with a predetermined ratio are ball-milled to obtain a composite powder, with a ball-to-material ratio of 6:1, a rotation speed of 200 r / min, and a ball-milling time of 2 h; S4, powder metallurgy sintering: including any one of the methods (1) SPS sintering; (2) vacuum hot pressing sintering, wherein: (1) SPS sintering: The composite powder obtained by mixing the raw materials in step S3 is pre-pressed at a pre-pressing pressure of 20 MPa for 30 seconds, and then SPS sintered at a vacuum degree of 80-200 Pa, a sintering pressure of 30 MPa, a sintering temperature of 1000-1150°C, a heating rate of 70°C / min, and a holding time of 10 min; then the temperature is reduced and the pressure is released to obtain a high-temperature resistant Fe-based self-lubricating composite material; (2) Vacuum hot pressing sintering: the composite powder obtained by mixing the raw materials in step S3 is pre-pressed at a pre-pressing pressure of 20 MPa for 30 seconds, and then vacuum hot pressing sintering is performed at a vacuum degree of 80-200 Pa, a sintering pressure of 30 MPa, a sintering temperature of 1000-1150°C, a heating rate of 70°C / min, a heat preservation time of 10 min, and then the temperature is reduced and the pressure is released to obtain a high temperature resistant Fe-based self-lubricating composite material; In the preparation method S3, the raw material mixing process for preparing the high temperature resistant Fe-based self-lubricating composite material composite powder requires pre-pressing.

[0008] In the preparation method, in step S4 of the powder metallurgy sintering method, after obtaining the blank by (1) spark plasma sintering and (2) vacuum hot pressing sintering, the prepared blank is subjected to surface grinding and deburring treatment to obtain a high temperature resistant Fe-based self-lubricating composite material.

[0009] Compared with the prior art, the present invention has the following beneficial effects: The preparation process of the high temperature resistant Fe-based self-lubricating composite material of the present invention, including raw material preparation, material mixing and sintering processes, is applicable to the preparation of all Fe-based self-lubricating composite materials.

[0010] The Fe alloy phase selected in the present invention can be mixed by directly adding metal element powder, and the material can be taken in the air, which can simplify the preparation process to a certain extent and reduce the production cost; The invention improves the mechanical properties of the composite material by utilizing the unique properties of the Fe material itself.

[0011] The addition of solid lubricating phase Ti3AlC2 can provide good lubrication effect, making it have a stable friction coefficient in the range of 25~500℃. 0.4 The addition of can improve the interface bonding between the phases and improve the mechanical properties of the composite material. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] The drawings described herein are used to provide a further understanding of the present invention and constitute a part of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings: Figure 1 This is a process flow chart of preparing a high temperature resistant Fe-based self-lubricating composite material according to an embodiment of the present invention; Figure 2 is the XRD pattern of the high temperature resistant Fe-based self-lubricating composite material obtained in Example 1; Figure 3 is a SEM image of the high temperature resistant Fe-based self-lubricating composite material obtained in Example 1; Figure 4 yes Figure 3 The atomic content percentage of each region; Figure 5 is a surface scan of the sintered body of the high temperature resistant Fe-based self-lubricating composite material obtained in Example 1; Figure 6 is a fracture morphology of a sintered body of a high temperature resistant Fe-based self-lubricating composite material obtained in Example 1; Figure 7 This is a friction and wear surface morphology of the high temperature resistant Fe-based self-lubricating composite sintered body obtained in Example 1; Figure 8 yes Figure 7 The percentage of A atoms in the middle region; Fig. 9 is a SEM image of the friction and wear fracture of the high temperature resistant Fe-based self-lubricating composite sintered body obtained in Example 1; Fig.10 is a surface morphology of a sintered body of a high temperature resistant Fe-based self-lubricating composite material obtained in Example 4; Fig.11 yes Fig.10 The atomic content percentage of each region in the Fig.12 is a room temperature friction and wear morphology of the high temperature resistant Fe-based self-lubricating composite material obtained in Example 4; Fig.13 is a surface morphology of a sintered body of a high temperature resistant Fe-based self-lubricating composite material obtained in Example 5; Fig.14 This is a room temperature friction and wear morphology of the high temperature resistant Fe-based self-lubricating composite material obtained in Example 5. DETAILED DESCRIPTION

[0013] It should be noted that, in the absence of conflict, the embodiments of the present invention and the features in the embodiments can be combined with each other. The described embodiments are only a part of the embodiments of the present invention, not all of the embodiments. The following description of at least one exemplary embodiment is actually only illustrative and is by no means any limitation to the present invention and its application or use. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention. Unless otherwise specifically stated, the relative arrangement of the steps described in these embodiments does not limit the scope of the present invention. The techniques, methods and equipment known to ordinary technicians in the relevant fields may not be discussed in detail, but in appropriate cases, the techniques, methods and equipment should be regarded as part of the authorization specification. In all examples shown and discussed here, any specific value should be interpreted as merely exemplary, not as a limitation. Therefore, other examples of exemplary embodiments may have different values.

[0014] The technical solutions in the embodiments of the present invention will be described clearly and completely below.

[0015] The invention discloses a Ti3AlC2 reinforced Fe-based composite self-lubricating composite material, which consists of an Fe alloy, a non-stoichiometric compound and a solid lubricating phase, wherein the non-stoichiometric compound comprises a non-stoichiometric nitride, carbide or boride of a transition metal; the solid lubricating phase comprises a ternary layered compound of the Mn+1AXn (n=1, 2, 3) family; in the high-temperature resistant Fe-based composite material, the mass fraction of the Fe alloy is 25-50wt.%, the mass fraction of the non-stoichiometric compound is 16.7-25wt.%, and the mass fraction of the solid lubricating phase is 33.3-50wt.%.

[0016] Non-stoichiometric compounds include non-stoichiometric nitrides, carbides or borides of transition metals (Ti, V, Cr, Zr, Nb, Mo, Hf, Ta, W).

[0017] Solid lubricants are MAX materials such as Ti3SiC2, Ti3AlC2, Ti2AlC, Ti2AlN, Ta2AlC, etc. The preparation of TiCx powder can be found in China: CN108754275B.

[0018] The solid lubricating phase is commercially available.

[0019] Figure 1 1 is a flow chart of the process for preparing the high temperature resistant Fe-based self-lubricating composite material according to the embodiment of the present invention, which will be specifically described below with reference to Embodiments 1 to 5. Example 1

[0020] High temperature resistant Fe-based self-lubricating composite material is composed of 35wt.% Fe alloy raw material and non-stoichiometric compound TiC 0.4The powder content is 16.67wt.% and the solid lubricating phase Ti3AlC2 particle content is 43.33wt.%. The preparation of Fe alloy powder can be found in China: CN109022992A, and the preparation of TiCx powder can be found in China: CN108754275B; then Fe alloy powder, TiCx powder and Ti3AlC2 particles are loaded into a steel ball mill according to proportion, and steel grinding balls are loaded according to the ball-to-material mass ratio of 6:1, and the ball milling mixture is carried out in an argon atmosphere (the speed is 200r / min, the ball milling time is 2h, and the machine is stopped for 30min every 1h for heat dissipation), and the material is taken out in a glove box; the diameters of the steel grinding balls are 8mm and 5mm respectively, and the mass ratio of large and medium balls is 6:1; the mixture is loaded into a graphite mold for pre-pressing, the pre-pressing pressure is 20MPa, and the pre-pressing is 30s. Then, SPS sintering was performed with a vacuum degree of 40 Pa and a pressure of 30 MPa. Then, it was heated from room temperature to 600 °C in 5 min and kept at 600 °C for 10 min. Then, the temperature was increased from 600 °C to 1100 °C at a heating rate of 70 °C / min and kept at that temperature for 10 min. The blank was cooled in the furnace and the surface of the blank was polished to obtain a high-temperature resistant Fe-based self-lubricating composite material. Figure 2-Figure 9 It can be seen that the density, hardness, friction coefficient and wear rate of the Fe-based self-lubricating composite material sample obtained at this time are 5.3 g / cm 3 , 10.1 GPa, 0.52 and 4.5×10 -9 mm 3 N -1 m -1 , 0.45 and 7.4×10 -9 mm 3 N -1 m -1 . Example 2

[0021] High temperature resistant Fe-based self-lubricating composite material is composed of Fe as raw material 50wt.%, non-stoichiometric compound TiC 0.4The powder content is 16.67wt.% and the solid lubricating phase Ti3AlC2 particle content is 33.33wt.%. The preparation of Fe alloy powder can be found in China: CN109022992A, and the preparation of TiCx powder can be found in China: CN108754275B; then Fe alloy powder, TiCx powder and Ti3AlC2 particles are loaded into a steel ball mill according to proportion, and steel grinding balls are loaded according to the ball-to-material mass ratio of 6:1, and the ball milling mixture is carried out in an argon atmosphere (the speed is 200r / min, the ball milling time is 2h, and the machine is stopped for 30min every 1h for heat dissipation), and the material is taken out in a glove box; the diameters of the steel grinding balls are 8mm and 5mm respectively, and the mass ratio of large and medium balls is 6:1; the mixture is loaded into a graphite mold for pre-pressing, the pre-pressing pressure is 20MPa, and the pre-pressing is 30s. Then SPS sintering was carried out with a vacuum degree of 40Pa and a pressure of 30MPa; then, it was heated from room temperature to 600℃ in 5min and kept at 600℃ for 10min; then the temperature was raised from 600℃ to 1150℃ at a heating rate of 70℃ / min and kept at this temperature for 10min. After cooling in the furnace, a blank was obtained. The surface of the blank was polished to obtain a high-temperature resistant Fe-based self-lubricating composite material. The density, hardness, room temperature friction coefficient and wear rate of the Fe-based self-lubricating composite material sample obtained at this time were 5.6g / cm 3 , 8.9 GPa, 0.65 and 5.6×10 -6 mm 3 N -1 m -1 . Example 3

[0022] The high temperature resistant Fe-based self-lubricating composite material is composed of 35 wt.% Fe alloy raw material and non-stoichiometric compound TiC 0.4The powder content is 32.5 wt.% and the solid lubricating phase Ti3AlC2 particle content is 32.5 wt.%. The preparation of Fe alloy powder can be found in China: CN109022992A, and the preparation of TiCx powder can be found in China: CN108754275B; then Fe alloy powder, TiCx powder and Ti3AlC2 particles are loaded into a steel ball mill according to the proportion, and steel grinding balls are loaded according to the ball-to-material mass ratio of 6:1, and the ball milling mixture is carried out in an argon atmosphere (the speed is 200r / min, the ball milling time is 2h, and the machine is stopped for 30min every 1h for heat dissipation), and the material is taken in a glove box; the diameters of the steel grinding balls are 8mm and 5mm respectively, and the mass ratio of large and medium balls is 6:1; the mixture is loaded into a graphite mold for pre-pressing, the pre-pressing pressure is 20MPa, and the pre-pressing is 30s. Then SPS sintering was carried out with a vacuum degree of 40Pa and a pressure of 30MPa; then, it was heated from room temperature to 600℃ in 5min and kept at 600℃ for 10min; then the temperature was raised from 600℃ to 1100℃ at a heating rate of 70℃ / min and kept at this temperature for 10min. After cooling in the furnace, a blank was obtained. The surface of the blank was polished to obtain a high-temperature resistant Fe-based self-lubricating composite material. The density, hardness, room temperature friction coefficient and wear rate of the Fe-based self-lubricating composite material sample obtained at this time were 5.4g / cm 3 , 10.7 GPa, 0.72 and 1.7×10 -8 mm 3 N -1 m -1 . Example 4

[0023] The high temperature resistant Fe-based self-lubricating composite material is composed of 35 wt.% of Fe alloy raw material, 11.81 wt.% of Ti powder, 9.86 wt.% of TiC powder and 43.33 wt.% of solid lubricating phase Ti3AlC2 particles. The preparation of Fe alloy powder can be found in China: CN109022992A, and then Fe alloy powder, TiC powder, Ti powder and Ti3AlC2 particles are proportionally loaded into a steel ball milling jar, and steel grinding balls are loaded according to the ball-to-material mass ratio of 6:1, and the ball milling mixture is carried out in an argon atmosphere (the speed is 200r / min, the ball milling time is 2h, and the machine is stopped for 30min every 1h for heat dissipation), and the material is taken in a glove box; the diameters of the steel grinding balls are 8mm and 5mm respectively, and the mass ratio of large and medium balls is 6:1; the mixed material is loaded into a graphite mold for pre-pressing, the pre-pressing pressure is 20MPa, and the pre-pressing is 30s. Then, SPS sintering was performed with a vacuum degree of 40Pa and a pressure of 30MPa. Then, it was heated from room temperature to 600℃ in 5min and kept at 600℃ for 10min. Then, the temperature was increased from 600℃ to 1100℃ at a heating rate of 70℃ / min and kept at this temperature for 10min. The blank was cooled in the furnace and the surface of the blank was polished to obtain a high temperature resistant Fe-based self-lubricating composite material. Figure 10-12 It can be seen that the density, hardness, room temperature friction coefficient and wear rate of the Fe-based self-lubricating composite material sample obtained at this time are 5.4 g / cm 3 , 10.6 GPa, 0.61 and 2.2×10 -8 mm 3 N -1 m -1 . Example 5

[0024] The high temperature resistant Fe-based self-lubricating composite material is composed of Fe powder 31.71 wt.%, Cu powder 2.45 wt.%, Cr powder 0.28 wt.%, Ni powder 0.56 wt.%, non-stoichiometric compound TiC 0.4The powder is 16.67 wt.% and the solid lubricating phase Ti3AlC2 particles are 43.33 wt.%. The preparation of Fe alloy powder can be found in China: CN109022992A, and the preparation of TiCx powder can be found in China: CN108754275B; then the Fe alloy powder, TiCx powder and Ti3AlC2 particles are loaded into the steel ball milling jar in proportion, and the steel grinding balls are loaded according to the ball-to-material mass ratio of 6:1, and the ball milling mixture is carried out in an argon atmosphere (the speed is 200r / min, the ball milling time is 2h, and the machine is stopped for 30min every 1h for heat dissipation), and the material is taken out in the glove box; the diameters of the steel grinding balls are 8mm and 5mm respectively, and the mass ratio of large and medium balls is 6:1; the mixture is loaded into a graphite mold for pre-pressing, the pre-pressing pressure is 20MPa, and the pre-pressing is 30s. Then, SPS sintering was performed with a vacuum degree of 40Pa and a pressure of 30MPa. Then, it was heated from room temperature to 600℃ in 5min and kept at 600℃ for 10min. Then, the temperature was increased from 600℃ to 1100℃ at a heating rate of 70℃ / min and kept at this temperature for 10min. The blank was cooled in the furnace and the surface of the blank was polished to obtain a high temperature resistant Fe-based self-lubricating composite material. Figure 13-Figure 14 It can be seen that the density, hardness, room temperature friction coefficient and wear rate of the Fe-based self-lubricating composite material sample obtained at this time are 5.4 g / cm 3 , 10.2 GPa, 0.51 and 1.5×10 -8 mm 3 N -1 m -1 .

[0025] In summary, the preparation process of the high temperature resistant Fe-based self-lubricating composite material of the present invention, including raw material preparation, mixing and sintering processes, is applicable to the preparation of all Fe-based self-lubricating composite materials. The Fe alloy phase selected in the present invention can be mixed by directly adding metal element powder, and the material can be taken in the air, which can simplify the preparation process to a certain extent and reduce production costs; the present invention improves the mechanical properties of the composite material with the unique properties of the Fe material itself. The addition of the solid lubricating phase Ti3AlC2 can provide a good lubrication effect, so that it has a stable friction coefficient in the range of 25~500℃. TiC 0.4 The addition of can improve the interface bonding between the phases and improve the mechanical properties of the composite material.

[0026] It should be noted that the non-stoichiometric compounds herein include non-stoichiometric nitrides, carbides or borides of transition metals (Ti, V, Cr, Zr, Nb, Mo, Hf, Ta, W). The solid lubricants herein are MAXFe materials such as Ti3SiC2, Ti3AlC2, Ti2AlC, Ti2AlN, Ta2AlC, etc. In this article, relational terms such as first and second are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variant thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such a process, method, article or device. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work belong to the scope of protection of the present invention.

[0027] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A Ti3AlC2 reinforced Fe-based composite self-lubricating composite material, which is composed of an Fe alloy, a non-stoichiometric compound and a solid lubricating phase, characterized in that: The non-stoichiometric compound comprises a non-stoichiometric nitride, carbide or boride of a transition metal; the solid lubricating phase comprises M n+1 AX n A ternary layered compound of the (n=1, 2, 3) family; the mass fraction of Fe alloy in the high temperature resistant Fe-based composite material is 25~50wt.%, the mass fraction of non-stoichiometric compounds is 16.7~25wt.%, and the mass fraction of solid lubricating phase is 33.3~50wt.%.

2. The Ti3AlC2 reinforced Fe-based composite self-lubricating composite material according to claim 1, characterized in that: The non-stoichiometric compounds include non-stoichiometric nitrides, carbides or borides of transition metals (Ti, V, Cr, Zr, Nb, Mo, Hf, Ta, W).

3. The Ti3AlC2 reinforced Fe-based composite self-lubricating composite material according to claim 1, characterized in that: The solid lubricant is a MAX material such as Ti3SiC2, Ti3AlC2, Ti2AlC, Ti2AlN, Ta2AlC, etc.

4. A Ti3AlC2 reinforced Fe-based composite self-lubricating composite material as claimed in claim 1, characterized in that: The preparation of TiCx powder can be found in China: CN108754275B.

5. A Ti3AlC2 reinforced Fe-based composite self-lubricating composite material as claimed in claim 1, characterized in that: The solid lubricating phase is commercially available.

6. A method for preparing the Ti3AlC2 reinforced Fe-based composite self-lubricating composite material as claimed in claim 1, characterized in that: These include but are not limited to the following two methods: S1. The preparation of composite powder includes two methods: a. Ball milling of Fe alloy powder (Fe powder, Cu powder, Cr powder and Ni powder), TiCx powder and Ti3AlC2 particles with a predetermined ratio in an argon atmosphere to obtain composite powder, the ball-to-material ratio is 6:1, the rotation speed is 200-400 r / min, and the ball milling time is 2-10 h; b. Ball milling of Fe powder, Cu powder, Cr powder, Ni powder, TiCx powder and Ti3AlC2 particles with a predetermined ratio in an argon atmosphere to obtain composite powder, the ball-to-material ratio is 6:1, the rotation speed is 200 r / min, and the ball milling time is 2-10 h; S2, pre-pressing: drying the mixed powder in an argon atmosphere or in air, and loading it into a mold for pre-pressing, wherein the pre-pressing pressure is 20 MPa, and the pre-pressing is performed for 30 seconds to obtain a pre-pressed raw material block; S3. There are two sintering methods for pre-pressed raw materials: (1) Spark plasma sintering (SPS): The pre-pressed raw material block is subjected to spark plasma sintering to obtain a blank specimen: First, a pressure of 30 MPa is slowly applied to the sample; then, the vacuum degree is evacuated to 80-200 Pa; then, it is heated from room temperature to 600 °C in 5 min, and kept at 600 °C for 10 min; then, the temperature is increased from 600 °C to 1000-1150 °C at a heating rate of 70 °C / min, and kept at this temperature for 10 min; then, it is cooled with the furnace to obtain a blank; the prepared blank is subjected to surface grinding and deburring treatment to obtain a high-temperature resistant Fe-based self-lubricating composite material; (2) Vacuum hot pressing sintering: The pre-pressed raw material block is subjected to vacuum hot pressing sintering to obtain a blank specimen; First, a pressure of 30 MPa is applied to the sample; then, the vacuum degree is evacuated to 80-200 Pa; then, the temperature is increased from room temperature to 900 °C at a heating rate of 20 °C / min. ℃, and keep it at 900 ℃ for 20 min; then increase the temperature from 900 ℃ to 1000-1150 ℃ at a heating rate of 70 ℃ / min, and keep it at that temperature for 10 min; cool with the furnace to obtain a blank, and perform surface grinding and deburring on the prepared blank to obtain a high-temperature resistant Fe-based self-lubricating composite material.

7. A method for preparing the Ti3AlC2 reinforced Fe-based high temperature resistant self-lubricating composite material as claimed in claim 6, characterized in that: The particle size of the metal element powder is 10-50 μm, the particle size of the non-stoichiometric compound powder is 20-50 μm, and the particle size of the solid lubricating phase particles is 90-900 μm.

Citation Information

Patent Citations

  • A TiAl-based high-temperature self-lubricating composite material and its preparation method

    CN108754275B

  • Fe-based high-temperature-resistant composite material containing multi-element lubricating phase and preparation method thereof

    CN109022992A